Rancang Bangun Aplikasi Data Siswa berbasis Desktop (Studi di SMK Ahmad Dahlan Cimanggu Cilacap) - cahyadi, hagni (Jurnal Teknologi dan Bisnis, 2020)
SMK Ahmad Dahlan Cimanggu Cilacap is a Vocational High School located in the city of Cilacap, Central Java. However, the data management of its students, employees, and finance was still using paper and physical records to be recapped using separated spreadsheet. The systems were not centered on a single management system, thus the employee often experienced difficulty in managing the student, employee and financial data. With that management model, inconsistencies in data between the student and financial frequently occured. This study developed an application designed for students, employees, and financial data management in SMK Ahmad Dahlan Cimanggu Cilacap. The system was designed using Unified Modeling Language and Entity Relationship Diagram. The developed system design includes the functionality such as students, employees, and financial data management and data reporting. The system provides access permissions based on access level owned by respective users. The result of this study is an integrated information system design for student, employee and financial data management in SMK Ahmad Dahlan Cimanggu Cilacap.